2021
DOI: 10.3390/min11090919
|View full text |Cite
|
Sign up to set email alerts
|

Wavefield Decomposition-Based Direct Envelope Inversion and Structure-Guided Perturbation Decomposition for Salt Building

Abstract: Due to the large-scale and strong perturbation features of salt bodies, it is very difficult to complete a good salt building with the conventional full waveform inversion (FWI) method without low-frequency data and prior information. The direct envelope inversion (DEI) method is quite effective for salt building when seismic data lack low-frequency information. However, in the current DEI studies, the calculation of the envelope field, which needs a nonlinear envelope operator, does not consider the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…When the seismic data lack low frequencies, it poses a great challenge for the traditional FWI to invert the deep-seated ore bodies [19][20][21][22][23][24][25][26][27]. This is because the reflection wave-based FWI misfit function shows strong nonlinear characteristics and leads to cycle skipping in the FWI process [10,11,28,32,38].…”
Section: Pafwi With Total-variation Regularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the seismic data lack low frequencies, it poses a great challenge for the traditional FWI to invert the deep-seated ore bodies [19][20][21][22][23][24][25][26][27]. This is because the reflection wave-based FWI misfit function shows strong nonlinear characteristics and leads to cycle skipping in the FWI process [10,11,28,32,38].…”
Section: Pafwi With Total-variation Regularizationmentioning
confidence: 99%
“…Zhang et al used the multisource FWI method to invert the ore bodies [18]. However, low-frequency seismic data below 6 Hz is still extremely important to retrieve low-wave-number structures and avoid cycle skipping of FWI [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…active seismic data in full, waveform inversion could obtain a suitable result for the highresolution seismic imaging of metal ore bodies. Zhang et al [9] proposed a structure-guided perturbation decomposition method, which can separate strong scattering salt information from direct envelope inversion results with the help of reverse time migration images. The numerical tests showed that the method is effective with good antinoise performance.…”
mentioning
confidence: 99%